PRODUKSI BAHASA TERTULIS MAHASISWA PENDERITA DISGRAFIA DI FAKULTAS ILMU BUDAYA UNIVERSITAS SAM RATULANGI - TANGKE, RIMA APRILIANA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research is entitled â€œWritten Language Production of Student with Disgraphia in Faculty of Humanity Sam Ratulangi Universityâ€. The objectives of this research are to describe dysgraphia itself and to analyze the influences of dysgraphia on the written language production of the student in Faculty of Humanity, Sam Ratulangi University. This research uses a descriptive method. There are three steps to finish this research, the first step is preparation. In this step, the writer reads the related theories of psycholinguistics in concern with language disorder, in this case dysgraphia. The second step is data collection. The writer gathers several students of English Student Association who are the participants of English debate and speech club, then examines them with the proper test suggested by Gvion and Friedman (2008:5). The third step is data analysis. The writer analyze the influences on the written language production of the student with dysgraphia by using the theories of Caplan (1992:192), Hatch (1983:1), Marcie dan Hecaen (1973:3), and Fanis dan Linda (2011:2). The results of this research show that dysgraphia is an impairment in writing which caused not only by the brain damaged but also by the cognitive and linguistic disorder. The student has a lexical dysgraphia. Dysgraphia also affects the written language production of the student orthographically. The student makes errors while writing, mostly the vowels. It does not affect his intelligent but his academic grade. Keywords : Psycholinguistics, Language Production, Language Disorder, Dysgraphia.